Remarkable Selectivity and Photo‐Cytotoxicity of an Oxidovanadium(IV) Complex of Curcumin in Visible Light. Issue 3 (23rd December 2014) - Banerjee, Samya; Dixit, Akanksha; Karande, Anjali A.; Chakravarty, Akhil R.
Abstract: Oxidovanadium(IV) complexes of 2‐(2′‐pyridyl)‐1, 10‐phenanthroline (pyphen), viz. [VO(pyphen)(acac)](ClO4 ) (1 ), [VO(pyphen)(anacac)](ClO4 ) (2 ) and [VO(pyphen)(cur)](ClO4 ) (3 ), where acac is acetylacetonate (in1 ), anacac is anthracenylacetylacetonate (in2 ) and cur is curcumin monoanion (in3 ) were synthesized, characterized and their photo‐induced DNA cleavage activities and photo‐cytotoxicities studied. The complexes are 1:1 electrolytes in DMF. The one‐electron paramagnetic complexes show a d‐d band near 760 nm in DMF. Complexes2 and3 are blue and green emissive, respectively, in DMSO. The complexes exhibit irreversible V IV /V III reductive responses near –1.1 V and V V /V IV oxidative responses near 0.85 V vs. SCE in DMF–0.1M TBAP. Complexes2 and3 display significant and selective photo‐cytotoxicity upon irradiation with visible light giving an IC50 value of about 5 μM against HeLa and MCF‐7 cancer cells; they are significantly less‐toxic against normal 3T3 control cells and in the absence of light. Complex1 was used as a control. Both cytosolic and nuclear localization of the complexes were observed on the basis of fluorescence imaging. The complexes, avid binders to calf thymus (ct) DNA, were found to photocleave supercoiled pUC19 DNA upon irradiation with near‐IR light (785 nm) by generating hydroxyl radical ( · OH) as the reactive oxygen species (ROS). Cell death events noted with HeLa and MCF‐7 cell lines likely are attributable to apoptotic pathways involving light‐assisted generation of intracellular ROS. Abstract : A curcumin oxidovanadium(IV) complex of pyphen is a potent metal‐based cytotoxin capable of inducing remarkable ROS‐mediated apoptotic photo‐cytotoxicity triggered by visible light (400–700 nm). This toxicity is selective for HeLa and MCF‐7 cancer cells relative to 3T3 control cells and is absent in the absence of light.